Про вплив скінченних початкових деформацій на поверхневу нестійкість нестисливого пружного шару, що взаємодіє з пів простором ідеальної рідини - Багно, О.М. (Доповіді НАН України, 2021)
На основі тривимірних лінеаризованих рівнянь теорії пружності скінченних деформацій для твердого тіла
та тривимірних лінеаризованих рівнянь Ейлера для ідеальної стисливої рідини побудовані дисперсійні
криві нормальних квазілембових хвиль у гідропружній системі в широкому діапазоні частот. Проаналізовано вплив скінченних початкових деформацій у нестисливому пружному шарі, а також півпростору ідеальної рідини на фазові швидкості, дисперсію квазілембових мод та поверхневу нестійкість гідропружного хвилеводу. Числові результати наведено у вигляді графіків та дано їх аналіз. The problem of the propagation of quasi-Lamb waves in a pre-deformed incompressible elastic layer that interacts
with the half-space of an ideal compressible fluid is considered. The study is conducted on the basis of
the three-dimensional linearized equations of elasticity theory of finite deformations for the incompressible elastic layer and on the basis of the three-dimensional linearized Euler equations for the half-space of an ideal
compressible fluid. The problem is formulated, and the approach based on the utilization of representations of
the general solutions of the linearized equations for an elastic solid and a fluid is developed. Applying the Fourier
method, we arrive at two eigenvalue problems for the equations of motion of the elastic body and the fluid.
Solving them, we find the eigenfunctions. Substituting the general solutions into the boundary conditions, we
obtain a homogeneous system of linear algebraic equations for the arbitrary constants. From the condition for
the existence of a nontrivial solution, we derive the dispersion equation. A dispersion equation, which describes
the propagation of normal waves in the hydroelastic system, is obtained. The dispersion curves for quasi-Lamb
waves over a wide range of frequencies are constructed. The effect of the finite initial deformations in an elastic
layer, the thickness of the elastic layer, and the half-space of an ideal compressible fluid on the phase velocities
and dispersion of quasi-Lamb modes are analyzed. It follows from the graphical material presented above that, in
the case of compression with 0.54, i.e., with a 46 percent’s reduction in the length of the highly elastic incompressible
body, the phase velocities of the surface waves (Stoneley waves and Rayleigh waves) vanish. This indicates
that surface instability develops at 0.54 for a highly elastic incompressible non-Hookean body initially in
a plane stress-strain state. We should point out that these figures agree with results obtained earlier in the theory
of stability and correspond to the critical value of the contraction parameter. In the case of highly elastic incompressible
bodies, the linearized wave theory makes it possible to study not only general and several specific
wave processes, but also the conditions under which the surface instability begins in elastic bodies and hydroelastic
systems. It also follows from the graphs that the ideal fluid slightly affects the surface instability of hydroelastic
systems. The numerical results are presented in the form of graphs, and their analysis is given.